Perancangan Interior Wine House Bar & Lounge di Surabaya - Dennis Sugianto; Lintu Tulistyantoro; yohan santoso (Intra, 2016)
The human lifestyles is one aspect that is growing rapidly. One example of lifestyle development is the start of entry and development of wine into modern society today. In this final project, the writer takes the theme Wine House Bar & Lounge, as a means of fulfilling the needs of those who are fond of wine. The place is meant not only as a place to relax but also a place to gather with others who have an interest or hobby towards wine, as well as to increase the appreciation of the wine itself. The design concept applied to the design of Wine House Bar & Lounge is “Complex Harmony”, where the designer wants to describe the complexity of the wine itself into every detail and design elements that create a harmonious design so that everyone who was in the room can be educated and get to know wine. In this design, the design method used is the method of data collection that includes literature study, observation, and survey.